Spatial and temporal characteristics of detonation wave propagation in silver azide; Combustion, Explosion, and Shock Waves; Vol. 51, iss. 3 - Kalenskii A. V.; Zvekov A. A.; Anan’eva M. V.; Kriger V. G.; Tsipilev V. P. Vladimir Papilovich; Razin A. V. Aleksey Valerievich (2015, 2015)
Title screen